(untitled) (ModaPalavra e-periódico, 2020)
The presentation of methods and techniques for the emotional study of products is proposed, with a clipping of research for fashion goods. The kansei engineering method wil l be explored in a descriptive and applied way, to help understand the emotions that users confer on products. Using focus group techniques, the objectives are to discuss the fashion and consequent selection of data to use with the method. In addition, the construction and application of the semantic differential scale will be used to record users’ emotional impressions. The results, obtained with the applied method associated with the techniques; aim to present the relationship between the interviewees’ em otional perception and design elements of the fashion goods that compose a clothing structure. Hence, the emotional significance attributed by users to products can be understood and converted into design requirements to develop new products. The presented method associated to the techniques is considered efficient and may be integrated to the practice of design